Do Milestone Ratings Predict Physical Medicine and Rehabilitation Board Certification Examination Scores?. (February 2021) - Francisco, Gerard E.; Yamazaki, Kenji; Raddatz, Mikaela; Sabharwal, Sunil; Robinson, Lawrence; Kinney, Carolyn; Holmboe, Eric
Abstract : Abstract: The Accreditation Council of Graduate Medical Education developed the Milestones to assist training programs in assessing resident physicians in the context of their participation in Accreditation Council of Graduate Medical Education–accredited training programs. Biannual assessments are done over a resident's entire training period to define the trajectory in achieving specialty-specific competencies. As part of its process of initial certification, the American Board of Physical Medicine and Rehabilitation requires successful completion of two examinations administered approximately 9 mos apart. The Part I Examination measures a single dimensional construct, physical medicine and rehabilitation medical knowledge, whereas Part II assesses the application of medical and physiatric knowledge to multiple domains, including data acquisition, problem solving, patient management, systems-based practice, and interpersonal and communication skills through specific patient case scenarios. This study aimed to investigate the validity of the Milestones by demonstrating its association with performance in the American Board of Physical Medicine and Rehabilitation certifying examinations. A cohort of 233 physical medicine and rehabilitation trainees in 3-yr residency programs (postgraduate year 2 entry) in the United States from academic years 2014–2016, who also took the American Board of Physical Medicine and Rehabilitation Parts I and II certifying examinations between 2016 and 2018, were included in the study. Milestones ratings in four distinct observation periods were correlated with scores in the American Board of Physical Medicine and Rehabilitation Parts I and II Examinations. Milestones ratings of medical knowledge (but not patient care, professionalism, problem-based learning, interpersonal and communication skills, and systems-based practice) predicted performance in subsequent Part I American Board of Physical Medicine and Rehabilitation Examination, but none of the Milestone ratings correlated with Part II Examination scaled scores. Abstract : Supplemental digital content is available in the text.